Associations between long-term blood pressure trajectory and all-cause and CVD mortality among old people in China - Liu, Huimeng; Wang, Yutong; Zhang, Binyan; Liu, Jingchun; Huo, Yating; Cao, Suixia; Wu, Shaowei; Wan, Yong; Xie, Xinming; Zeng, Lingxia; Yan, Hong; Dang, Shaonong; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Optimal blood pressure (BP) management strategy among the elderly remains controversial, with insufficient consideration of long-term BP trajectory. This study aimed to identify BP trajectory patterns as well as terminal BP trajectory among the Chinese elderly and to explore the relationships between BP trajectories trajectory and all-cause mortality and CVD mortality.We included 11,181 participants older than 60 at baseline (mean age, 80.98±10.71) with 42,871 routine BP measurements from the Chinese Longitudinal Healthy Longevity Survey. Latent class trajectory analysis and Cox proportional hazard model were conducted to identify trajectory patterns and their association with mortality. Furthermore, we also applied mixed-effects model to identify terminal BP trajectories among the elderly.Compared with stable at normal high level trajectory, uncontrolled excess systolic BP (SBP) trajectory with decreasing trend was associated with a 34% (HR=1.34, 95% CI: 1.23-1.45) higher risk of all-cause mortality. Considering the competing risk of non-CVD death, uncontrolled excess BP trajectory with decreasing trend had a more pronounced effect on CVD mortality, in which HR This is a provisional file, not the final typeset article (95% CI) was 1.67 (1.17, 2.37). Similar results were also found in diastolic BP (DBP), pulse pressure (PP), and mean arterial pressure (MAP) trajectories. We further conducted a mixed-effects model and observed that SBP and PP trajectories first increased and began to decline slightly six years before death. In contrast, DBP and MAP showed continuous decline 15 years before death.Long-term uncontrolled BP trajectory was associated with all-cause mortality, especially CVD mortality. Keeping a stable BP over time may be an important way for CVD prevention among the elderly.